2023
DOI: 10.1139/as-2021-0042
|View full text |Cite
|
Sign up to set email alerts
|

Combining community observations and remote sensing to examine the effects of roads on wildfires in the East Siberian boreal forest

Abstract: The paper is aimed at assessing the associations between the road networks geography and dynamics of wildfire events in the East Siberian boreal forest. We examined the relationship between the function of roads, their use, and management and the wildfire ignition, propagation and termination during the catastrophic fire season of 2016 in the Irkutsk Region of Russia. Document analysis and interviews were utilized to identify main forest users and road infrastructure functional types and examine wildfire manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…These findings align with the findings of other authors [55,60,61]. For example, Danilović et al [53] found that morphometric factors had an important role in forest road planning. However, the authors of the referenced study primarily focused their attention on analyzing the effects of slope and exposure of the terrain.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings align with the findings of other authors [55,60,61]. For example, Danilović et al [53] found that morphometric factors had an important role in forest road planning. However, the authors of the referenced study primarily focused their attention on analyzing the effects of slope and exposure of the terrain.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with many studies, such as Kuklina et al [53] and Zambon et al [50], which considered the capacity of forest roads to provide accessibility within the forest in a dual way: both as an ignition source (e.g., arson) and as an essential support for fire suppression (e.g., delineation of potential firefighting operations).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, of course, if production is declining, the local budget income is reduced. -Changes in transport and geographical locations through the development of a technological road network lead, on one hand, to new opportunities for remote communities, new routes, and improved accessibility, but on the other hand, there are new problems associated with large numbers of newcomers entering these areas and changes in the wildfire hazard situation in the boreal forest [74] (especially relevant to D, E, and F).…”
Section: F Villages Of Intersettlement Area 8mentioning
confidence: 99%